Factors Associated with Providing Complete Basic Immunization in Toddlers - Handiny, Febry; Tari, Meysi Neldian; Oresti, Syalvia (Journal of Health Sciences and Epidemiology, 2023)
Complete basic immunization (CBI) in toddlers is a crucial aspect of public health. It can protect children from infections that can kill or disable them. Nevertheless, the CBI is still low in the working area of Lubuk Buaya Public Health Center, standing at 49.7%, while the national target achievement is 95%, indicating a disparity of 45.3%. The purpose of this study was to determine the factors associated with the provision of complete basic immunization to toddlers in Pasia Nan Tigo Village, Lubuk Buaya Public Health Center Working Area. The type of research was quantitative with a cross-sectional design. The researchers conducted the study from March to August 2023. The population of this study were mothers who had toddlers who were residing in Pasia Nan Tigo Village, as many as 105 people. Accidental sampling was used to collect 51 respondents. We obtained data by questionnaire and interview. We analyzed the data using the chi-square test. The result found that 58.8% of respondents did not provide complete basic immunization to toddlers, 64.7% of respondents had a low level of knowledge, 60.8% of respondents did not have available facilities and infrastructure, 62.7% of respondents stated that the role of health workers was not satisfying, and 62.7% of respondents did not get family support. The level of knowledge, availability of facilities and infrastructure, the role of health workers, and family support were associated with the provision of complete basic immunization in toddlers. Knowledge, facilities and infrastructure, health workers, and family support are factors that can influence the provision of complete basic immunization for toddlers. It is expected for the head of the Lubuk Buaya Public Health Center to complete Integrated Healthcare Center tools such as reading materials, brochures, and leaflets so that Integrated Healthcare Center services can motivate cadres to change the mother’s behavior. Keywords: CBI, Knowledge, Facilities and Infrastructure, Health Worker, Family Support ,